Primary caregiver's experiences in caring paranoid schizophrenia patients: A qualitative study - Alwin Issac; Renjulal Yesodharan; Leena Sequira (Clinical Epidemiology and Global Health, 2023)
Background: Mental disorders are accompanied by tremendous suffering for the patient and caregiver and can bring forth significant disability. A descriptive phenomenological study was conducted to explore primary caregiver's experiences of caring for patients diagnosed with paranoid schizophrenia. Methods: Caregivers were selected as study participants if they were the patient's family members and the primary caregiver for the patient for the past six months. The participants were recruited through maximum variation sampling, and the researcher used a semi-structured interview guide to collect the data from the participants. Codes were identified, patterns analyzed, and themes were recorded using Braun and Clarke's six phases of thematic analysis. Results: The study found that the mean age of the participants was 47 years, and the duration of caregiving ranged from one to three years. Major themes identified from the study were: encountering gloom, challenges in caregiving, expectations, and coping strategies. Conclusion: Caregivers of paranoid schizophrenic patients have significant challenges during their everyday lives. Whereas caregivers who receive adequate support from their family members and community better cope with their daily challenges.